IMPLEMENTASI KEBIJAKAN PELAYANANPERTIMBANGAN TEKNIS PERTANAHAN DI KANTOR PERTANAHAN KABUPATEN TUBAN - Suryadi, Bambang (Universitas 17 Agustus 1945 Surabaya, 2015)
Services technical considerations of land is one of an element of public service in alloffices of the National Land Agency included in the National Land Agency Tuban.Services technical considerations of land are the terms and conditions of use and the useof land as the basis for the issuance of location permits, and permits the designation ofland use changes. This study concentrated on technical considerations ministry of land,especially in the issuance of location permits. This study used qualitative researchmethods. The research objective is to analyze the implementation and performance ofservice personnel land technical considerations in the issuance of location permits theLand Office (BPN) Tuban. The results showed that the implementation andperformance of officers of technical services technical considerations land land in theissuance of location permits the Land Office (BPN) Tuban regency is relatively good.Yet still needed improvements to improve services to the public. There are stillimprovements to resources including human resources both in quantity and quality.Similarly, they need to increase both internal and external communications, bothbetween leaders and subordinates, an officer in BPN, as well as with external parties areinstitutions or other agencies and the public. BPN officials still need to maximizepenginformasian to the public related to persoaaln procedures, timing, completenessletter to licensing as well as on the necessary funds. Necessary transparency andoptimization of information so that the public as users of the service can be satisfied.Keywords: Policy Implementation, Service, Technical Considerations Land